Relativistic expansion of a magnetized fluid - Gourgouliatos, K. N.; Vlahakis, N. (2010)
We study semi-analytical time-dependent solutions of the relativistic MHD equations for the fields and the fluid emerging from a spherical source. We assume uniform expansion of the field and the fluid and a polytropic relation between the density and the pressure of the fluid. The expansion velocity is small near the base but approaches the speed of light at the light sphere where the flux terminates. We find self-consistent solutions for the density and the magnetic flux. The details of the solution depend on the ratio of the toroidal and the poloidal magnetic field, the ratio of the energy carried by the fluid and the electromagnetic field and the maximum velocity it reaches.
Keywords: Astrophysics - High Energy Astrophysical Phenomena; Physics - Plasma Physics